Adsorption of anionic dye onto magnetic FeO/CeO nanocomposite: Equilibrium, kinetics, and thermodynamics - Shaomin Gao; Wenwen Zhang; Zhaohui An; Shulin Kong; Donghui Chen (Adsorption Science & Technology)
In this study, a magnetically separable Fe 3 O 4 /CeO 2 (Fe/Ce) nanocomposite is synthesized by sol-precipitation method and characterized by field-emission scanning electron microscopy, transmission electron microscopy, X-ray diffraction, energy dispersive spectrometer , vibrating sample magnetometer, atomic absorption spectrometer, and zeta potential measurements. The Fe/Ce is used as sorbent to adsorb anionic dye of Acid Black 210 (AB210) from aqueous solutions, and the maximum adsorption capacity is about 90.50 mg/g, which is six times higher than that of the commercial CeO 2 . Dependence of absorption performance on essential factors, such as initial dye concentration, temperature and initial pH, are experimentally examined. The result shows that the adsorption kinetic of Fe/Ce follows pseudo-second-order model and the adsorption isotherm is well described by the Langmuir adsorption model. Furthermore, the thermodynamic analysis indicates that the adsorption of Fe/Ce for AB210 is spontaneous and endothermic.